A functional magnetic resonance imaging examination of audiovisual observation of a point-light string quartet using intersubject correlation and physical feature analysis - Lillywhite, Amanda; Nijhof, Dewy; Glowinski, Donald; Giordano, Bruno L.; Camurri, Antonio; Cross, Ian; Pollick, Frank E. (Frontiers in Neuroscience, 2022)
We use functional Magnetic Resonance Imaging (fMRI) to explore synchronized neural responses between observers of audiovisual presentation of a string quartet performance during free viewing. Audio presentation was accompanied by visual presentation of the string quartet as stick figures observed from a static viewpoint. Brain data from 18 musical novices were obtained during audiovisual presentation of a 116 second performance of the allegro of String Quartet, No 14 in D minor by Schubert played by the ‘Quartetto di Cremona’. These data were analyzed using intersubject correlation (ISC). Results showed extensive ISC in auditory and visual areas as well as parietal cortex, frontal cortex and subcortical areas including the medial geniculate and basal ganglia (putamen). These results from a single fixed viewpoint of multiple musicians are greater than previous reports of ISC from unstructured group activity but are broadly consistent with related research that used ISC to explore listening to music or watching solo dance. A feature analysis examining the relationship between brain activity and physical features of the auditory and visual signals yielded findings of a large proportion of activity related to auditory and visual processing, particularly in the superior temporal gyrus (STG) as well as midbrain areas. Motor areas were also involved, potentially as a result of watching motion from the stick figure display of musicians in the string quartet. These results reveal involvement of areas such as the putamen in processing complex musical performance and highlight the potential of using brief naturalistic stimuli to localize distinct brain areas and elucidate potential mechanisms underlying multisensory integration.